ASPEK ASSURANCE TERHADAP KEPUASAN PELANGGAN DAN MINAT MENGINAP KEMBALI PADA HOTEL PAN PACIFIC NIRWANA BALI RESORT - I Made Bayu Wisnawa (Institut Pariwisata dan Bisnis Internasional, 2011)
The Hotel is business accommodation managed commercially by providing services to customers/guests for their satisfaction, thus expected to be created repeat business. Tabanan has only one five-star hotel, Pan Pacific Nirwana Bali Resort, which is the pride of the community Tabanan. An effort to keep this going concern hotels even win the competition is to provide a good quality service through aspects of assurance. This research aims to (i) acknowledge the influence aspects of assurance of customer satisfaction. (ii) acknowledge the influence of aspect of assurance to the customer's interest to stay back and (iii) acknowledge the influence of customer satisfaction to the customer's interests to stay back . The questionaire that is given to the customers is 200, but there is only 159 questionaries and fullfiled requirement for analysis. The hypothesis was tested by using a statistical technique of structural equation model with AMOS 8 and SPSS 11.5. Models has meet the requirements of SEM (Structural Equation Modelling), with χ2 value of chi square (353,135), the probability of significance (0,087), RMSEA (0.016), CMIN / DF (1.007), TLI (0.987), CFI (0.998), RMR (0.075) and GFI (0.905). The test results showed that: (i) assurance aspect has positive and significant impact on customer satisfaction (regression coefficient 0,4423 and 0.0297 in probability ), (ii) assurance aspect has positive and significant impact on interest to live again (regression coefficient 0.384 on the probability of 0.0289), (iii) customer satisfaction has positive and significant impact on interest to keep coming back again (regression coefficient of 0.2099 at 0.0495 probability). Suggestions that is given for management are : (i)keep maintain marketing strategy,(ii)more attention in assurance aspect to develop service quality construct such as : the english skill of hotel employees,faithful hotel staff , the convenience of customers feel services of hotel staffs , the increase of the officers ; and service and the cook ( chef ) capable of preparing dishes according to your taste in a row has estimated value of the biggest . For next research, hopefully could improve the object research into the hotels in one tourism area or more and improve the variable related to service quality, customer satisfaction and customer’s loyalty, such as trust and marketing mix.